Pandangan dan pengalaman pengajar terkait siniar sebagai media mengajar saat pandemi Covid-19 - Nunik Triana; Irwansyah Irwansyah (Islamic Communication Journal, 2021)
This study elaborates on how lecturers perceive podcasts in the teaching process and their experience using this media in distance learning during the co-19 pandemic. By first describing the concept of podcasts as a convergence medium and their use in the education sector, the writer elaborates problems with a descriptive qualitative approach and involved five lecturers a research subjects. Research founds that the use of podcast was able to help lecturers conduct a distance teaching during the co-19 pandemic. Itâ€™s because the cost of accessing podcasts is cheap; can be accessed in locations with inadequate telecommunications infrastructure; making teaching material via podcasts are easy, inexpensive, and more personalized; podcasts can be listened to at any time, multimedia, and can be a replay. Because the nature of the podcast is not interactive and visual so to achieve the learning target lecturers usually use other supporting media that function as a discussion tool between lecturers and students. Although considered effective, podcasts have not been able to replace the effectiveness of traditional face-to-face teaching methods, in this case, podcasts can be used as a supplement.Â